2016
DOI: 10.14740/jem333w
|View full text |Cite
|
Sign up to set email alerts
|

Plasma B-Type Natriuretic Peptide Levels May Increase Because of Fat Mass Loss by Metformin or Sodium-Glucose Transporter 2 Inhibitors Treatment

Abstract: Background: Cardiovascular disease (CVD) is the leading cause of death in type 2 diabetes. Metformin reduces cardiovascular events in obese patients with type 2 diabetes, and sodium-glucose transporter 2 (SGLT2) inhibitors decrease cardiovascular events in type 2 diabetic patients with established CVD. However, the underlying mechanisms behind the cardioprotective effects of metformin and SGLT2 inhibitors are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…four months treatment with metformin reduced the BNP level in patientswith heart failure compared with non-treated patients (14). Also, its reported that treatment with metformin for 3 months lead to decrease the BNP level significantly when compared with nontreated rats (15). Matrix metalloproteinase is a protease involved in the tissue remodelling in both pathological and physiological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…four months treatment with metformin reduced the BNP level in patientswith heart failure compared with non-treated patients (14). Also, its reported that treatment with metformin for 3 months lead to decrease the BNP level significantly when compared with nontreated rats (15). Matrix metalloproteinase is a protease involved in the tissue remodelling in both pathological and physiological conditions.…”
Section: Discussionmentioning
confidence: 99%